Increasing Students' Engagement through Cooperative Learning (2022)
ABSTRACT: This action research study conducted at a public institution located in Medellín, Antioquia was aimed at exploring the impact of cooperative learning as a strategy to increase seventh graders' engagement in the English class. Data were collected through a research journal, video recordings, mini surveys, a focus group, and an interview with the cooperating teacher of the institution. The analysis shows that cooperative learning is an effective strategy to increase the students’ emotional engagement as it can foster positive feelings such as happiness, interest and satisfaction. Additionally, this strategy has a beneficial impact on the students’ cognitive engagement because they can gain understanding of the content more easily as they help each other when their language limitations keep them from advancing. However, in relation to the students’ behavioral engagement, the analysis showed no consistency in the findings because at some points they were engaged and behaved, but there were situations where their behavior was inappropriate. It would be worth conducting research on these topics, but under different circumstances; for example, in safer places with less time restrictions.